Impact of Script-Based Improvisation on Students' Speaking Skills at SMA Muhammadiyah Pangsid - Lababa Lababa; Sam Hermansyah; Rustam Efendy Rasyid; Aswadi Aswadi; Usman M (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to investigate the effect of Script-Based Improvisation on students’ speaking achievement at SMA Muhammadiyah Pangsid. The research compared the speaking performance of students taught using Script-Based Improvisation and those taught using the conventional memorization technique. A quantitative approach was employed, with two groups of eleventh-grade students selected through Cluster Random Sampling. The experimental group was taught using Script-Based Improvisation, while the control group utilized the memorizing dialogue technique. After six sessions of treatment, both groups were administered a post-test to assess their speaking abilities. The data were analyzed using descriptive and inferential statistics, with the results showing that the experimental group outperformed the control group. The mean score for the experimental group was higher, and t-test analysis revealed a significant difference between the two groups. This indicates that Script-Based Improvisation significantly improved students' speaking achievement compared to the conventional memorization method.